2020
DOI: 10.3342/kjorl-hns.2019.00759
|View full text |Cite
|
Sign up to set email alerts
|

Update on Clinical Manifestation in Acute Low-Tone Hearing Loss

Abstract: Background and Objectives Acute low-tone hearing loss (ALHL) is gaining attention as an independent disease identity with close association with endolymphatic hydrops and early stage Meniere’s disease (MD). This study aims to compare patients of ALHL with patients exhibiting low-tone hearing loss and ear fullness without vertigo in various audio-vestibular assessments and in progression to overt MD.Subjects and Method A total of 249 patients with low-tone hearing loss with ear fullness without vertigo was enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…ALHL can be diagnosed by pure tone audiometry examination. [9][10][11][12] In this instance, the patient complained of buzzing in both ears, feeling full in both ears and losing hearing. The patient made no claims of feeling lightheaded.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…ALHL can be diagnosed by pure tone audiometry examination. [9][10][11][12] In this instance, the patient complained of buzzing in both ears, feeling full in both ears and losing hearing. The patient made no claims of feeling lightheaded.…”
Section: Discussionmentioning
confidence: 86%
“…7 According to Kim, most victims are female, with a peak age of 40. 12 ALHL without vertigo was described by Taki et al as a unique type of ISSNHL. Despite this, multiple studies have linked cochlear hydrops and ALHL to the early onset of Meniere's illness.…”
Section: Discussionmentioning
confidence: 99%
“…One additional study 17 was identified within the references of one of the full‐texts and manually added to the full‐text review. Among all full‐texts reviewed, 41 studies 3–8,10,13,16–18,22–51 were determined to meet the study inclusion and exclusion criteria and these studies subsequently underwent data extraction (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Several other studies have shown that patients with ALHL have an elevated SP/AP ratio on electrocochleography (ECoG), and some progress to Meniere’s disease (MD). Therefore, endolymphatic hydrops (EH), as in MD, has emerged as an important etiology of ALHL [ 6 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have shown that patients with ALHL have an elevated SP/AP ratio on electrocochleography (ECoG), and some progress to Meniere's disease (MD). Therefore, endolymphatic hydrops (EH), as in MD, has emerged as an important etiology of ALHL [6][7][8][9]. The confirmation of actual EH requires a post-mortem histological examination; therefore, this method has limitations in clinical practice when managing living patients.…”
Section: Introductionmentioning
confidence: 99%